Vocabulaires de l'Afrique australe, recueillis par des explorateurs portugais - Gamitto, Antonio Candido Pedroso, 1806-1866.
Volume (82 pages) containing a manuscript vocabulary.
Portuguese army officer.
Collection material in African dialects, with French, and Portuguese.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: African languages -- Dialects; African languages -- Vocabulary; Portuguese -- Africa; Africa -- Description and travel; Army officers